High‐throughput screening of argan oil composition and authenticity using benchtop 1H NMR. (6th April 2020) - Gunning, Yvonne; Jackson, Alex J.; Colmer, Joshua; Taous, Fouad; Philo, Mark; Brignall, Rachel M.; El Ghali, Tibari; Defernez, Marianne; Kemsley, E. Kate
Abstract: We use 60‐MHz benchtop nuclear magnetic resonance (NMR) to acquire 1 H spectra from argan oils of assured origin. We show that the low‐field NMR spectrum of neat oil contains sufficient information to make estimates of compositional parameters and to inform on the presence of minor compounds. A screening method for quality and authenticity is presented based on nearest‐neighbour outlier detection. A variety of oil types are used to challenge the method. In a survey of retail‐purchased oils, several instances of fraud were found. Abstract : We use 60‐MHz benchtop nuclear magnetic resonance (NMR) to acquire 1 H spectra from argan oils of assured origin. We show that the low‐field NMR spectrum of neat oil contains information sufficient for obtaining composition values and informing on the presence of minor compounds. A screening method for quality and authenticity is presented based on nearest‐neighbour outlier detection. A variety of oil types are used to challenge the method. In a survey of retail‐purchased oils, several instances of fraud were found.